Capacity Decay Mechanism of Microporous Separator‐Based All‐Vanadium Redox Flow Batteries and its Recovery. Issue 2 (29th October 2013) - Li, Bin; Luo, Qingtao; Wei, Xiaoliang; Nie, Zimin; Thomsen, Edwin; Chen, Baowei; Sprenkle, Vincent; Wang, Wei
Abstract The results of the investigation of the capacity decay mechanism of vanadium redox flow batteries with microporous separators as membranes are reported. The investigation focuses on the relationship between the electrochemical performance and electrolyte compositions at both the positive and negative half‐cells. Although the concentration of total vanadium ions remains nearly constant at both sides over cycling, the net transfer of solution from one side to the other and thus the asymmetrical valance of vanadium ions caused by the subsequent disproportionate self‐discharge reactions at both sides lead to capacity fading. Through in situ monitoring of the hydraulic pressure of the electrolyte during cycling at both sides, the convection was found to arise from differential hydraulic pressures at both sides of the separators and plays a dominant role in capacity decay. A capacity‐stabilizing method is developed and was successfully demonstrated through the regulation of gas pressures in both electrolyte tanks.